WHO SPEAKS FOR WHOM?: REPRESENTATION, IDENTITY POLITICS, AND THE ETHICS OF CASTING IN CONTEMPORARY INDIAN THEATRE - Naik, Babuli (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper interrogates the contested politics of embodiment and voice within contemporary Indian theatre, with particular attention to the ethical stakes of casting practices as they intersect with structures of caste, gender, and queer identity. Framed by the critical provocation— “Who speaks for whom?”—the study situates the theatrical stage as a charged site of cultural mediation where questions of visibility, authority, and legitimacy are continuously negotiated. Drawing on the theoretical interventions of Judith Butler’s performativity, Gayatri Chakravorty Spivak’s subaltern critique, and Rustom Bharucha’s reflections on interculturalism, the inquiry foregrounds the tensions between artistic agency and the moral imperative of representational justice. Through close analyses of selected performances that centre Dalit, transgender, and queer experiences, the paper interrogates the asymmetries of access, authorship, and affect that shape contemporary dramaturgical practices. It further attends to the role of audience reception and the politics of spectatorship in legitimizing or contesting representational claims. Ultimately, the paper advances a decolonial ethics of casting—one grounded in self-representation, epistemic accountability, and collaborative authorship—urging Indian theatre to confront its complicities and reimagine itself as a site of affective solidarity, critical resistance, and ethical enactment.